Challenges for Latin American Social Psychology: contributions from feminist perspectives - Barrantes Requeno, Brenda (2023)
Introduction: Latin America is facing a socio-political and economic context of great violence and crisis of care, reproduction of life, bonds and social fabric, with women being one of the most vulnerable groups. Therefore, it is necessary for social psychology, as a discipline permeated by neoliberalism and patriarchy, to turn its gaze and pay more attention, on the one hand, to the complex problems caused by political violence in our region and, on the other, to be critically examined to implement substantial transformations to its own research, academic education and social action or university extension processes. [Continue reading in the article]